Synergistic effect between ultraviolet irradiation and electrochemical oxidation for removal of humic acids and pharmaceuticals. (28th January 2019) - García‐Espinoza, Josué Daniel; Zolfaghari, Mehdi; Mijaylova Nacheva, Petia
Abstract: The fate of pharmaceuticals in the aquatic environment is significantly affected by the presence of humic acids (HA). In this work, the synergistic effect of electrochemical oxidation (EO) and ultraviolet irradiation (UVI) was evaluated for HA removal and for the simultaneous degradation of three pharmaceuticals (carbamazepine, propranolol and sulfamethoxazole) in presence of HA. The effectiveness of EO, UVI and their combination for HA removal was assessed using different operating parameters, such as type of anode (Nb/BDD and Ti/IrO2 ), supporting electrolyte (NaCl, NaBr and Na2 SO4 ), current density (8.1, 16.1, 28.2, 40.3, and 48.4 mA/cm 2 ), pH (3, 7 and 9) and NaCl electrolyte concentration (7, 14 and 21 mM). The use of non‐active anode Nb/BDD, NaCl electrolyte and combination EO‐UVI was the most efficacious option for HA removal, due to the production of hydroxyl radicals as well as active chlorine species (HClO, Cl ● and ClO − ) generated by anodic oxidation and by UVI. The effectiveness of the EO process was enhanced coupling EO with UVI, however the energetic consumption increased. The composition of the electrolyte was the pivotal parameter since a complete degradation of the pharmaceuticals was achieved by both processes EO and EO‐UVI using NaCl as electrolyte; this is attributed to the indirect oxidation by electrogenerated active chlorine which dominates the pharmaceuticals degradation.